2007
DOI: 10.1515/cclm.2007.095
|View full text |Cite
|
Sign up to set email alerts
|

Pro12Ala polymorphism of the peroxisome proliferator-activated receptor-γ2 (PPARγ-2) gene is associated with greater insulin sensitivity and decreased risk of type 2 diabetes in an Iranian population

Abstract: Our results for a sample of Iranian type 2 diabetes cases and controls provide evidence that the Pro/Ala genotype of the PPARgamma-2 gene is associated with insulin sensitivity and may also have protective role against type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
2
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 45 publications
1
16
2
1
Order By: Relevance
“…Nine cohort studies [12,25,26,27,28,29,30,31,32], 7 population case-control studies [33,34,35,36,37,38,39], 31 cross-sectional studies [5,7,10,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67], and 9 interventional studies [8,68,69,70,71,72,73,74,75] were included in the meta-analysis of the association between PPARγ Pro12Ala polymorphism and obesity. The characteristics and results of the studies are summarized in table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine cohort studies [12,25,26,27,28,29,30,31,32], 7 population case-control studies [33,34,35,36,37,38,39], 31 cross-sectional studies [5,7,10,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67], and 9 interventional studies [8,68,69,70,71,72,73,74,75] were included in the meta-analysis of the association between PPARγ Pro12Ala polymorphism and obesity. The characteristics and results of the studies are summarized in table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Each dataset was treated as a separate comparison in the meta-analysis. Forty studies were on Caucasians [5,8,10,12,25,26,27,28,29,32,33,34,35,36,37,38,39,41,42,43,45,46,47,48,52,53,54,57,60,61,62,63,64,65,66,67,68,69,70], 10 studies were on Asian [31,40,49,50,55,56,58,59,71,72] and 6 studies were on mixed populations [7,30,37,73,74,75]. Between 56 studies, 19 studies provided data on male [10,12,29,33,35,37,40,42,43,47,50,57,60,61,62,65,66,69,71] and 22 studies on female members [10,12,29,32,37,41,42,50,53,54,55,59,60,61,62,64,66,…”
Section: Resultsmentioning
confidence: 99%
“…Various studies establish functional alterations related to proline or to alanine changes: the change in the functional binding domain of peroxisome proliferatoractivated receptor-gamma 2 (PPARG2) protein, where alanine is related to resistance to development of diabetes in humans (Meshkani et al, 2007); the change in the catalytic subunit of 1,3-β-d-glucan synthase (Fks1p) gene of Candida parapsilosis that gives resistance to antifungal drugs (Garcia-Effron et al, 2008); and the proline to alanine change at the cyclooxygenase-2 (COX-2) gene associated with the risk of breast cancer (Li et al, 2009). Moreover, Pera et al (2008) observed that the addition or omission of a proline or a charged AA in the solute carrier family 26 member 4 (SLC26A4) protein is detrimental to its function.…”
Section: Discussionmentioning
confidence: 99%
“…However, although PPAR γ is associated with IR and type II diabetes, the 12Ala allele does not reduce the risk of diabetes in South Asians, Chinese, and Malaysians [168, 169]. The 12Pro-161T haplotype is associated with lower body mass index (BMI) and lower fasting serum triglycerides (TGs) in Koreans but not in Iranians [170, 171]. In a meta-analysis of BMI subgroups, the Ala allele was shown to be associated with an increase in 0.96 units for BMIs of 35 or more, and this association was observed in individuals with BMIs of 27 to less than 35 or with BMIs of 35 or more when the meta-analysis was restricted to Caucasians [172]; this pattern was not found in Asians.…”
Section: Nutrigenetics and Pparγ Polymorphismsmentioning
confidence: 99%